The costs of living at the edge: Seasonal stress in wild savanna-dwelling chimpanzees. Issue 121 (August 2018) - Wessling, Erin G.; Kühl, Hjalmar S.; Mundry, Roger; Deschner, Tobias; Pruetz, Jill D.
Abstract: Adaptations associated with shifting from a predominately forested habitat to a more open environment are considered a crucial step in hominin evolution. Understanding how chimpanzees, one of our closest-living relatives, are exposed to the selection pressures associated with living in a relatively sparse, hot, and dry environment can inform us about the relative importance of potential environmental stressors involved in adaptations to drier environments. We investigated the extent to which chimpanzees living in an extreme savanna habitat experience seasonal variability in either energy balance or thermoregulation (dehydration and heat exposure), as well as whether these potential environmental constraints are taxing to chimpanzee individuals. Specifically, we tested the hypothesis that savanna environments impose seasonally-relevant costs to chimpanzees. To this end, we collected 368 urine samples from one community of chimpanzees at Fongoli, Senegal, and measured c-peptide, creatinine, and cortisol as measures of physiological responses to environmental food, water, and heat constraints, respectively. We then evaluated the influence of climatic and phenological factors on these indicators. Results illustrated significant seasonal variation in all biomarkers, which corresponded to relevant ecological correlates. Furthermore, creatinine but not c-peptide correlated with cortisol levels, suggesting that chimpanzees in this environment endure periods of heat and dehydration stress, but are able to avoid stressful levels of negative energy balance. Using savanna chimpanzees as a referential model, our research lends support to the notion that thermoregulatory challenges were a significant factor in hominin evolution, and suggests these challenges may have overshadowed the challenges of maintaining adequate energetic balance during the expansion of the hominin range from wetter to drier environments.